1997
DOI: 10.1111/j.1530-0277.1997.tb03772.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption by Young Actively Growing Rats: A Histomorphometric Study of Cancellous Bone

Abstract: Alcohol consumption by young actively growing rats has been previously demonstrated to decrease bone density. This study addresses the mechanism of alcohol action on the early phases of bone growth and development using histomorphometric techniques. Four-week-old, female Sprague-Dawley rats were divided into three groups. Alcohol-treated animals were fed a modified Lieber-DeCarli diet ad libitum containing 35% ethanol-derived calories, whereas the pair-fed animals (weight-matched to ethanol rats) received an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
32
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 52 publications
8
32
2
Order By: Relevance
“…This is in agreement with other studies that examined cortical width (Dyer et al, 1998;Sampson, 1998;Hogan et al, 1999;Wezeman et al, 1999). However, this is in contrast to histomorphometric studies that have demonstrated lower trabecular volume, width, and connectivity in alcohol-consuming animals (Sampson et al, 1997;Sampson, 1998;Wezeman et al, 1999;Dai et al, 2000;Turner, 2000;Hogan et al, 2001). This apparent discrepancy may be due to the resolution limits of the pQCT, which is unable to discern individual trabeculae (volume averaging), and/or to the reduced time of ethanol exposure in study 2.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…This is in agreement with other studies that examined cortical width (Dyer et al, 1998;Sampson, 1998;Hogan et al, 1999;Wezeman et al, 1999). However, this is in contrast to histomorphometric studies that have demonstrated lower trabecular volume, width, and connectivity in alcohol-consuming animals (Sampson et al, 1997;Sampson, 1998;Wezeman et al, 1999;Dai et al, 2000;Turner, 2000;Hogan et al, 2001). This apparent discrepancy may be due to the resolution limits of the pQCT, which is unable to discern individual trabeculae (volume averaging), and/or to the reduced time of ethanol exposure in study 2.…”
Section: Discussioncontrasting
confidence: 55%
“…Ethanol's effects on the skeleton have been examined through studies using biomechanical, histomorphological, molecular, and mineral quantitative techniques. Studies have demonstrated inhibition of bone growth (Sampson et al, 1997), reduced mineral density (Turner, 2000), and reduced bone strength (Hogan et al, 2001). The skeletal changes that result from alcohol consumption seem to be independent of liver damage or calciotropic hormone levels, and there is much evidence that ethanol acts directly on osteoblast activity .…”
mentioning
confidence: 99%
“…The detrimental effects on bone metabolism that we observed are consistent with earlier studies [39][40][41][42]. Alcohol is a potent inhibitor of bone growth in rats and decreases peak bone mass [39][40][41][42].…”
Section: Discussionsupporting
confidence: 92%
“…These reductions in bone growth contribute to a decrease in bone mass. Similar changes were observed by Sampson and colleagues in growing female Sprague Dawley rats fed alcohol (Sampson et al 1996;Hogan et al 1997;Sampson et al 1997;Sampson & Spears 1999). Fig.…”
Section: Effects Of Alcohol On the Skeleton In Growing Ratssupporting
confidence: 75%